1993
DOI: 10.1002/pd.1970130111
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal sonographic diagnosis of metastatic neuroblastoma: Report of a case and review of the literature

Abstract: Congenital malignant tumours are rare. Neuroblastoma is the most common solid tumour, accounting for about 30-50 per cent of tumours evident during the neonatal period. A case of metastatic, rapidly growing neuroblastoma, diagnosed prenatally by ultrasound at 32 weeks' gestation, is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 9 publications
1
25
0
Order By: Relevance
“…Such complications previously have been linked to metastatic neuroblastoma with high circulating catecholamines levels. 9 The presence of a suprarenal mass did not influence the mode of delivery and had no repercussions on the conditions of birth.…”
Section: Discussionmentioning
confidence: 99%
“…Such complications previously have been linked to metastatic neuroblastoma with high circulating catecholamines levels. 9 The presence of a suprarenal mass did not influence the mode of delivery and had no repercussions on the conditions of birth.…”
Section: Discussionmentioning
confidence: 99%
“…Thoracic solid masses were described by De Filipi et al [2] and Estroff et al [3] in 1 case each. Jaffa et al [6] were the first to mention findings in the liver. Suresh et al [19] diagnosed a cerebral neuroblastoma confirmed by biopsy.…”
Section: Localisationmentioning
confidence: 99%
“…De Filipi et al [2] and Ferraro et al [4] observed that the masses grew during pregnancy. In 1 case, Jaffa et al [6] described calcification of the liver, abnormal growth of the fetal abdomen, and a prenatal hydrocele. Postnatally, these findings appeared to be metastases of a neuroblastoma of the thoracic sympathicus.…”
Section: Consistency Of the Tumourmentioning
confidence: 99%
See 1 more Smart Citation
“…In neonates, US can depict intraspinal components of neuroblastoma [30]. Presently, there is also a role for US in the prenatal diagnosis of neuroblastoma [12,18,19,23,24,26,32]. Diculties occasionally occur in the dierential diagnosis of nephroblastoma (Wilms tumour) [8,27,30].…”
Section: Introductionmentioning
confidence: 99%